Knowledge and technology adoption, diffusion, and transfer international perspectives - Zolait, Ali Hussein Saleh, 1972-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book is filled with original scientific and quality research articles on management information systems, technology diffusion, and business systems application aspects of e-commerce, e-government, and mobile application"--Provided by publisher.
Harnessing information and communication technologies for diffusing connected government applications in developing countries: concept, problems and recommendations / E. Ruhode, V. Owei -- An efficient and simple algorithm for matrix inversion / Ahmad Farooq, Khan Hamid -- Thirst for business value of information technology / Govindan Marthandan, Tang Chun Meng -- Adoption of short messaging service (SMS) in Malaysia / Ainin Sulaiman, Ali Hussein Saleh Zolait -- A study of the systemic relationship between worker motivation and productivity / J. J. Haefner, Christos Makrigeorgis -- E-government initiative in the Sultanate of Oman: the case of Ubar / Khamis Al-Gharbi, Ahmed Al-Kindi -- Mobile commerce use among UK mobile users: an experimental approach based on a proposed mobile network utilization framework / Asem Moqbel, Mirella Yani-De-Soriano, Shumaila Yousafzai -- An efficient and generic algorithm for matrix inversion / Ahmad Farooq, Khan Hamid, Inayat Ali Shah -- Saving DBMS resources while running batch cycles in data warehouses / Nayem Rahman -- Internet adoption from omani organizations' perspective: motivations and reservations / Khamis Al-Gharbi, Ahlam Abdullah AlBulushi -- Electronic training methods: relative effectiveness and frequency of use in the Malaysian context / Veeriah Sinniah, Sharan Kaur -- Problems of initiating international knowledge transfer: is the Finnish living lab method transferable to Estonia? / Katri-Liis Lepik, Merle Krigul, Erik Terk -- Mobile commerce use among UK mobile users based on a proposed mobile network utilization framework: an experimental approach - part 2 / Asem Moqbel, Mirella Yani-Di-Soriano, Shumaila Yousafzai -- A study on the internet security and its implication for e-commerce in Yemen / Ali Hussein Saleh Zolait, Abdul Razak Ibrahim, Ahmad Farooq -- Supply chain management practices and firm performance: an empirical study of the electronics industry in Malaysia / Abdul Razak Ibrahim, Ali Hussein Zolait, Veera Pandiyan Sundram -- Traditional job-related factors and career salience in IT-based workplace / Aminu Ahmad, Hartini Ahmad -- The impact of technology anxiety on the use of mobile financial applications / Cheon-Pyo Lee -- The influence of internet security on e-business competence in Jordan: an empirical analysis / Amin A. Shaqrah -- Human talent forecasting using data mining classification techniques / Hamidah Jantan, Abdul Ali Hamdan, Zulaiha Othman -- Computing gamma calculus on computer cluster / Hong Lin, Jeremy Kemp, Padraic Gilbert -- Determinants of the use of knowledge sources in the adoption of open source server software / Kris Ven, Jan Verelst.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed May 8, 2012).
Keywords: Knowledge management; Management information systems; Information technology -- Management; Technology transfer; Diffusion of innovations; Business data communications; Diffusion of innovation models; Distributed databases and networks; E-services; Evaluation of MIS; Graphics and Web design; Performance analysis; System analysis; Technology acceptance; Telecommunications; Web technology; Electronic books